Obrigaç\~oes futuras com a previdência dos servidores públicos municipais: Análise longitudinal - Bernardo Patta Schettini (Instituto de Pesquisa Econômica Aplicada (IPEA), 2017)
– This paper calculates indexes for the funding levels of municipal retirement systems in Brazil using actuarial valuations and budget reports aiming to test hypotheses regarding the reasons which have driven underfunding in the past years notwithstanding the 1998 and 2003 reforms and the greater supervision exercised by the federal government since 2004. Data are for the years of 2008 and 2012. The results are in line with the tax-smoothing hypothesis and show that electoral politics may be relevant, although part of the variation is related to general trends. ln times of fiscal deterioration, the incumbent chooses to accumulate pension liabilities rather than increasing taxation or cutting other expenses. More candidates relative to the number of seats in the legislative chamber reduces the intertemporal deficit. Mayors enjoying support from the majority of the councilmen improve the long-run position, but the lame-duck ones care less about the local pension fund.
Keywords: D72; H21; H75; 330; public employees' retirement systems; municipalities; funding levels; tax-smoothing; electoral politics